P356 Safety and effectiveness of granulocyte and monocyte adsorptive apheresis in paediatric patients with inflammatory bowel disease: a multi-centre cohort study. (25th January 2019) - Toita, N; Tanaka, H; Arai, K; Shimizu, H; Abukawa, D; Kobayashi, T; Yoshimura, N; Tanida, S; Hosoi, E
Abstract: Background: The usefulness of granulocyte and monocyte adsorptive apheresis (GMA) in paediatric patients with inflammatory bowel disease (IBD) has not been studied in depth. We investigated the safety and effectiveness of GMA in paediatric patients with IBD who participated in a post-marketing surveillance study referred to as the PARTICULAR study. Methods: The PARTICULAR study was a retrospective, multi-centre cohort study that included patients with ulcerative colitis (UC) or Crohn's disease (CD) who received GMA between November 2013 and March 2017. The study enrolled patients with at least one special situation, including paediatric, being elderly, with anaemia and concomitant treatment with multiple immunosuppressants. Patients aged >18 years were excluded from this study. The GMA was performed using Adacolumn® (JIMRO, Takasaki, Japan). Each patient underwent up to 11 GMA sessions. All adverse events (AEs) were recorded during the observation time interval. Any AE, for which the causality of the GMA could not be ruled out was classified as an adverse device effect (ADE). In addition, feasibility problems (FPs) during the operation of the GMA column were recorded. The effectiveness of GMA was assessed in UC patients with a partial Mayo (pMayo) score of ≥3. Remission was defined as a pMayo score of ≤2. Patients receiving concomitant treatment with infliximab, adalimumab or calcineurin inhibitors were excluded from the effectiveness assessment. Results: A total of 53 paediatric patients (40 UC, 13 CD) from 27 institutions, with a mean age of 15.0 years, were included. The incidence of AEs, ADEs and FPs were 18.9%, 5.7% and 20.8%, respectively. The ADEs included abdominal discomfort in 2 (3.8%) patients and one patient each with fever, nausea/vomiting and headache (1.9% each). The FPs included blood access failure in 10 patients (18.9%), venous pressure elevation in 4 (7.5%), clot formation in the apheresis lines in 2 (3.8%) and venous access difficulty in 1 patient (1.9%). A total of 17 patients (32.1%) discontinued GMA therapy ahead of the planned treatment schedule. Among these patients, the GMA therapy was discontinued for the following reasons: (1) decision by the physician ( n = 12), (2) withdrawal due to AE ( n = 4) and (3) withdrawal by own wish ( n = 1); none were discontinued due to ADE and FP. The effectiveness of the GMA was assessed in 29 UC patients. The remission rate of the paediatric UC patients was 43.5%. Conclusions: There were AEs and FPs in approximately 20% of paediatric patients with IBD treated by GMA, but none of these discontinued the GMA treatment due to ADE or FP. Remission was achieved by GMA in 44% of the paediatric UC patients. This study showed that GMA was well tolerated treatment option for the paediatric IBD patients.